Clinical, genetic aspects and molecular pathogenesis of osteopetrosis - D. D. Nadyrshina; R. I. Khusainova (Вавиловский журнал генетики и селекции)
Osteopetrosis (“marble bone”, ICD-10-78.2) includes a group of hereditary bone disorders distinguished by clinical variability and genetic heterogeneity. The name “osteopetrosis” comes from the Greek language: ‘osteo’ means ‘bone’ and ‘petrosis’ means ‘stone’, which characterizes the main feature of the disease: increased bone density caused by imbalances in bone formation and remodeling, leading to structural changes in bone tissue, predisposition to fractures, skeletal deformities. These defects, in turn, affect other important organs and tissues, especially bone marrow and the nervous system. The disease can be autosomal recessive, autosomal dominant, X-linked or sporadic. Autosomal dominant osteopetrosis has an incidence of 1 in 20,000 newborns and autosomal recessive one has 1 in 250,000. To date, 23 genes have been described, structural changes in which lead to the development of osteopetrosis. Clinical symptoms in osteopetrosis vary greatly in their presentation and severity. The mildest skeletal abnormalities are observed in adulthood and occur in the autosomal dominant form of osteopetrosis. Severe forms, being autosomal recessive and manifesting in early childhood, are characterized by fractures, mental retardation, skin lesions, immune system disorders, renal tubular acidosis. Clinical examination and review of radiographs, bone biopsy and genetic testing provide the bases for clinical diagnosis. The early and accurate detection and treatment of the disease are important to prevent hematologic abnormalities and disease progression to irreversible neurologic consequences. Most patients die within the first decade due to secondary infections, bone marrow suppression and/or bleeding. This article summarizes the current state of the art in this field, including clinical and genetic aspects, and the molecular pathogenesis of the osteopetrosis.